2017
DOI: 10.1021/acs.jafc.6b04408
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to a Mediterranean Diet Influences the Fecal Metabolic Profile of Microbial-Derived Phenolics in a Spanish Cohort of Middle-Age and Older People

Abstract: Despite the evidence regarding the influence of certain polyphenol food sources on the metabolic profile in feces, the association between the different phenolics provided by the diet and the fecal phenolic profile has not been elucidated. In this study, the composition of phenolic metabolites in fecal solutions was analyzed by UPLC-ESI-MS/MS in 74 volunteers. This fecal phenolic profile showed a high interindividual variation of the different compounds analyzed, phenylacetic and phenylpropionic acids being th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 61 publications
4
73
0
5
Order By: Relevance
“…Several studies have also recently demonstrated that adherence to a Mediterranean-style diet is associated with beneficial gut microbiota characteristics, including higher biodiversity, over-representation of Prevotella , and under-representation of opportunistic pathogens [ 52 , 53 , 54 , 55 ].…”
Section: Gut Microbiota: the Neglected Actor In Aging?mentioning
confidence: 99%
“…Several studies have also recently demonstrated that adherence to a Mediterranean-style diet is associated with beneficial gut microbiota characteristics, including higher biodiversity, over-representation of Prevotella , and under-representation of opportunistic pathogens [ 52 , 53 , 54 , 55 ].…”
Section: Gut Microbiota: the Neglected Actor In Aging?mentioning
confidence: 99%
“…149 Moreover, interaction of GIT microbes with dietary phytochemicals is a bidirectional loop, which promotes microbial diversity and reduces systemic oxidative stress and inflammatory burden. 150,151 Geographic variations in childhood gut colonization patterns have been implicated in differential risk for allergy and autoimmunity for many years 152 ; however, new metagenomic analyses add a new dimension to this story, revealing striking differences in dominant LPS variants produced by fecal bacteria of children from regions with a high prevalence of allergy and early-onset autoimmunity. 153 Children from regions with more prevalent immune disease (Finland) show LPS subtypes with markedly reduced immunogenicity derived from Bacteroides species compared with LPS derived largely from Escherichia coli in children from areas of lower disease prevalence (Russia), reflecting recognized differences in relative species abundance.…”
Section: Nutrition As a Centerpiecementioning
confidence: 99%
“…Prebiotics: selectively stimulate the growth of beneficial bacteria and might offer protection against effects of AGEs as shown in a human trial [46] Fiber: Short chain fatty acids (SCFAs) are produced through the fermentation of polysaccharides and improve gut barrier function via its effect on IL-22 (promoting mucus production) as shown in murine models [47,48] Fiber: Short chain fatty acids (SCFAs) are produced through the fermentation of polysaccharides and reduce allergic inflammation as shown in murine models [47,48] Polyphenols: Increase gut microbial diversity [49,50] indicated by human studies Emulsifiers e.g., polysorbate 80 and carboxymethylcellulose may destroy the epithelial mucous layer in the gut as shown in mice [51] Emulsifiers e.g., polysorbate 80 and carboxymethylcellulose, promote inflammation as shown in mice [51] Emulsifiers e.g., polysorbate 80 and carboxymethylcellulose, alter gut microbial composition as shown in mice [51] (D) Food Preparation/Production…”
Section: Gut Barrier Function Inflammation Microbiomementioning
confidence: 99%